Context Is Routinely Encoded During Emotion Perception - Barrett, Lisa Feldman; Kensinger, Elizabeth A. (Psychological Science, 2010)
In the present study, we investigated whether context is routinely encoded during emotion perception. For the first time, we show that people remember the context more often when asked to label an emotion in a facial expression than when asked to judge the expression’s simple affective significance (which can be done on the basis of the structural features of the face alone). Our findings are consistent with an emerging literature showing that facial muscle actions (i.e., structural features of the face), when viewed in isolation, might be insufficient for perceiving emotion.